Allelic variant in the anti-müllerian hormone gene leads to autosomal and temperature-dependent sex reversal in a selected nile tilapia line - Stephan Wessels (2018)
Owing to the demand for sustainable sex-control protocols in aquaculture, research in tilapia sex determination is gaining momentum. The mutual influence of environmental and genetic factors hampers disentangling the complex sex determination mechanism in Nile tilapia (Oreochromis niloticus). Previous linkage analyses have demonstrated quantitative trait loci for the phenotypic sex on linkage groups 1, 3, and 23. Quantitative trait loci for temperature-dependent sex reversal similarly reside on linkage group 23. The anti-Müllerian hormone gene (amh), located in this genomic region, is important for sexual fate in higher vertebrates, and shows sexually dimorphic expression in Nile tilapia. Therefore this study aimed at detecting allelic variants and marker-sex associations in the amh gene. Sequencing identified six allelic variants. A significant effect on the phenotypic sex for SNP ss831884014 (p < 0.0017) was found by stepwise logistic regression. The remaining variants were not significantly associated. Functional annotation of SNP ss831884014 revealed a non-synonymous amino acid substitution in the amh protein. Conseq uently, a fluorescence resonance energy transfer (FRET) based genotyping assay was developed and validated with a representative sample of fish. A logistic linear model confirmed a highly significant effect of the treatment and genotype on the phenotypic sex, but not for the interaction term (treatment: p < 0.0001; genotype: p < 0.0025). An additive genetic model proved a linear allele substitution effect of 12% in individuals from controls and groups treated at high temperature, respectively. Moreover, the effect of the genotype on the male proportion was significantly higher in groups treated at high temperature, giving 31% more males on average of the three genotypes. In addition, the groups treated at high temperature showed a positive dominance deviation (+11.4% males). In summary, marker-assisted selection for amh variant ss831884014 seems to be highly beneficial to increase the male proportion in Nile tilapia, especially when applying temperature-induced sex reversal. © 2014 Wessels et al.